Mapping the feedback landscape: a systematic review of research on feedback sources, methods, and technologies in preservice teacher education - Okumu, Michael; Lammert, Catherine; Gokmen, Ceren; Mule, Felix (Frontiers in Education, 2025)
Feedback is widely recognized as a cornerstone of effective teacher education that functions as a critical bridge between conceptual knowledge and instructional practice. In the context of preservice teacher education, feedback supports teacher candidates’ development of instructional competence by providing targeted suggestions for improvement. Although existing literature offers insight into various feedback practices, there remains a lack of holistic synthesis examining how feedback is sourced, delivered, and mediated through technology. This systematic literature review, guided by Hattie and Timperley’s (2007) Feedback Model, analyzed 45 peer-reviewed empirical studies published between 2014 and early 2025. Findings revealed that the most studied feedback type by source is instructor-provided feedback (n = 25), followed by peer (n = 8), mixed-source (n = 8), and technology-only feedback (n = 2) and that written feedback is the most studied feedback method. Although some studies employed advanced technologies such as video annotations, AI simulations, and real-time coaching tools, most of the reviewed studies did not report using any specific technology to support feedback. This finding suggests the field’s ongoing interest in studying relatively traditional feedback methods despite the potential of value of peer feedback and the availability of scalable, interactive, and cost-effective feedback technologies.